The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1111/j.1365-2222.2007.02676.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the composition of intestinal Bifidobacterium species and the development of allergic diseases in infants in rural Japan

Abstract: Our results in infants in rural Japan support the hypothesis that a compositional difference in intestinal Bifidobacterium species may be associated with the development of allergy in early infancy, although the responsible species might vary among countries or races.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 14 publications
4
49
0
1
Order By: Relevance
“…Annunziato et al [47] demonstrated that Th17 cells play critical roles in the pathogenesis of Crohn’s disease. The oral administration of LAB has been reported to improve the clinical symptoms of Crohn’s disease [48], suggesting that the suppression of CCL20 by LAB found in this study may reflect the mechanisms underlying this clinical observation, at least in part.…”
Section: Discussionmentioning
confidence: 76%
“…Annunziato et al [47] demonstrated that Th17 cells play critical roles in the pathogenesis of Crohn’s disease. The oral administration of LAB has been reported to improve the clinical symptoms of Crohn’s disease [48], suggesting that the suppression of CCL20 by LAB found in this study may reflect the mechanisms underlying this clinical observation, at least in part.…”
Section: Discussionmentioning
confidence: 76%
“…It is well documented that early bacterial colonization patterns are associated with antibody production in the gut (Suzuki et al, 2007), and that the variation of microbiota modestly influences the host gene expression (Rawls et al, 2006). However, there is little information regarding interaction between the host gene expression and the structure of gut microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence shows that probiotics induce several beneficial host responses by blocking pathogenic effects of invasive bacteria and inhibiting excessive responses in innate immunity, thus supporting intestinal epithelial cell homeostasis [2]. Cross-sectional/prospective cohort studies indicated that allergic children were less often colonized with Bifidobacterium than non-allergic children [3,4,5,6,7,8,9,10]. Recent clinical trials have suggested that probiotic bacteria decrease and prevent allergic symptoms, especially in atopic dermatitis [11,12].…”
Section: Introductionmentioning
confidence: 99%